Mediated sense of place: effects of mediation and mobility on the place perception of German professionals in Singapore - Bork-Hüffer, Tabea (New media & society, 2016)
This article examines the differences that digital media (Internet and mobile communications) and mobility create for sense of place. Based on in-depth interviews with 30 German professionals in Singapore, it analyses digital media choices and use during the relocation and settlement process in the destination of migration and the effect of these practices on migrants’ perception of place. It demonstrates how the primary reason to use digital media conversed from individual interests and needs in relation to the relocation and/or initial exploration of the city to the social and emotional ramifications of their use the longer the interviewees stayed in Singapore. It makes a theoretical contribution to the understanding of how digital and offline places combine in the construction of sense of place, how the digital sphere affects engagements with place, attachment to it and sensuous experiences of it.